2023
DOI: 10.1002/ccd.30611
|View full text |Cite
|
Sign up to set email alerts
|

Transvenous retrograde thoracic duct embolization for effective treatment of recurrent plastic bronchitis after fontan palliation

Abstract: We report the case of a 5.5-year-old patient (16 kg/105 cm) who presented with plastic bronchitis (PB) refractory to conservative treatment 3 months after completion of Fontan palliation. Bi-inguinal transnodal fluoroscopy-guided lymphangiogram confirmed the chylous leak originating from the thoracic duct (TD) into the chest and did not opacify any central lymphatic vessel for direct transabdominal puncture. Retrograde transfemoral approach was adopted to catheterize the TD and selectively embolize its caudal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In the paediatric population, secondary chylopericardium can be caused by systemic infection, Volume 9; Issue 01 Cardiolog Res Cardiovasc Med, an open access journal ISSN: 2575-7083 malignancy including lymphoma, and most commonly trauma or surgery [16]. Idiopathic chylopericardium can rarely be caused by thoracic lymph vessel anomalies as is seen in our case [17,18].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In the paediatric population, secondary chylopericardium can be caused by systemic infection, Volume 9; Issue 01 Cardiolog Res Cardiovasc Med, an open access journal ISSN: 2575-7083 malignancy including lymphoma, and most commonly trauma or surgery [16]. Idiopathic chylopericardium can rarely be caused by thoracic lymph vessel anomalies as is seen in our case [17,18].…”
Section: Discussionmentioning
confidence: 65%
“…Embolization involves deploying embolic material (typically n-BCA glue, coils, or both) directly into the thoracic duct (nonselective embolization) or into an abnormal lymphatic channel (selective embolization) [23]. One study demonstrated a 75% clinical success rate in managing nontraumatic chylous effusions, including nontraumatic chylopericardium, with clinical success being measured as no recurrence of effusion [17]. Embolization with access via catheterization was ultimately the most effective treatment for our patient, with resolution of pericardial effusion on postoperative imaging.…”
Section: Discussionmentioning
confidence: 99%
“…During interstage catheterization of patients with modified surgical Norwood procedures, SM would also fasten transarterial cannulation of banded pulmonary arteries that originate usually high and posteriorly within the pulmonary homograft ( 26 ). It could also be a game changer for transvenous retrograde thoracic duct cannulation and embolization in Fontan patients with recurrent plastic bronchitis ( 27 ). In addition, Soyama et al described a new technique of compact coil packing for the target vessels with the use of intentional folding by the bendable tip of the SM ( 8 ).…”
Section: Discussionmentioning
confidence: 99%